SISTEM INFORMASI PENJUALAN PADA BLAST COMPUTAMA PURWOREJO - Damar Eko Cahyono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
The development of information technology is very rapid, very instrumental in everyday life. In the development of Blast Computama currently still using the manual system in recording sales transactions and service, which is still using thestock book to record inventory and still use the notes to record sales and service transactions. With the above problemshow to design sales information system, on Blast Computama. Based on the above problem formulation, the purpose of research is to build a sales information system that is useful tofacilitate the recording of inventory and sales and service transactions. In designing and building sales informationsystems, required data required. How to get the data by interview, observation, literature study and system requirementanalysis needed. The design of the system performed to produce a sales and service applications on Blast Computama in accordance withthe needs of the company. Outputs from the sales system are inventory recording, sales and service memos, sales andservice report.